2008
DOI: 10.1007/s00267-008-9151-1
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitating Agricultural Streams in Australia with Wood: A Review

Abstract: Worldwide, the ecological condition of streams and rivers has been impaired by agricultural practices such as broadscale modification of catchments, high nutrient and sediment inputs, loss of riparian vegetation, and altered hydrology. Typical responses include channel incision, excessive sedimentation, declining water quality, and loss of in-stream habitat complexity and biodiversity. We review these impacts, focusing on the potential benefits and limitations of wood reintroduction as a transitional rehabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 109 publications
3
50
0
2
Order By: Relevance
“…Raymond and Vondracek [76], for example, suggested a positive correlation between a stable river bank and the macroinvertebrate assemblage by converting conventional grazing to rotational grazing in farming. Similar to land use management, Lester and Boulton [77] also suggested that bank stability can be improved through the exclusion of grazing animals from river banks and revegetation of the river banks.…”
Section: Biotic Integrity and Potential Restoration Actionsmentioning
confidence: 99%
“…Raymond and Vondracek [76], for example, suggested a positive correlation between a stable river bank and the macroinvertebrate assemblage by converting conventional grazing to rotational grazing in farming. Similar to land use management, Lester and Boulton [77] also suggested that bank stability can be improved through the exclusion of grazing animals from river banks and revegetation of the river banks.…”
Section: Biotic Integrity and Potential Restoration Actionsmentioning
confidence: 99%
“…While providing beneficial services in terms of wind-driven wave erosion mediation and ecological functions using tree debris (e.g. habitat and biodiversity enhancement) warrants engineering, the efficacy and collateral ecological functions observed in rivers (Larson et al, 2001;Lester and Boulton, 2008) are often lacking in estuarine and coastal applications.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Woody debris are often added directly in the channel, and new woody plants have been reintroduced along the river course to address the lack of any riparian vegetation on riverbanks in cultural landscapes (Reich et al 2003). Both instream and riparian wood enhancement may improve the diversity of fish and macroinvertebrates, increase storage of organic material and sediment, and strengthen bank stability (Lester and Boulton 2008). Compared to other restoration techniques, such measures have logistical advantages and generally require low costs and low maintenance.…”
Section: Common Restoration Measures Improving the Morphological Charmentioning
confidence: 99%